Verification of Electromagnetic Calorimeter Concept for the HADES spectrometer. (March 2015) - Svoboda, O; Blume, C; Czyžycki, W; Epple, E; Fabbietti, L; Galatyuk, T; Golubeva, M; Guber, F; Hlaváč, S; Ivashkin, A; Kajetanowic, M; Kardan, B; et al.
Abstract: The HADES spectrometer currently operating on the beam of SIS18 accelerator in GSI will be moved to a new position in the CBM cave of the future FAIR complex. Electromagnetic calorimeter (ECAL) will enable the HADES@FAIR experiment to measure data on neutral meson production in heavy ion collisions at the energy range of 2-10 A GeVon the beam of the new accelerator SIS100. Calorimeter will be based on 978 massive lead glass modules read out by photomultipliers and a novel front-end electronics. Secondary gamma beam with energies ranging from 81 MeV up to 1399 MeV from MAMI-C Mainz facility was used to verify selected technical solutions. Relative energy resolution was measured using modules with three different types of photomultipliers. Two types of developed front-end electronics as well as energy leakage between neighbouring modules under parallel and declined gamma beams were studied in detail.